A Journey of Land Restoration and Prosperity in Life for Rural Farmers - Singh, Ramesh; Garg, Kaushal K.; Anantha K.H.; Venkataradha A.; Shukla, Ashok; Seshadri, Arun (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The Bundelkhand region in Uttar Pradesh has long struggled with water scarcity and drought, leaving vast areas of land barren and farmers facing uncertain futures. To combat this, the Department of Agriculture, UP Government, partnered with ICRISAT Hyderabad to launch a massive land restoration and holistic development initiative across 40 villages in the Jhansi district. By implementing a mix of traditional and modern rainwater harvesting techniques such as renovating Havelis, constructing check dams, and widening natural drains, the project successfully captured monsoon rains to recharge the depleted groundwater table, ensuring water availability where it was needed most. The results of this intervention have been transformative for the local community, turning a semi-arid zone into a productive agricultural hub. Over 6,000 previously dry wells were revived, and approximately 11,000 hectares of fallow land were brought back under cultivation, which helped double the farmers' incomes and significantly curb distress migration. This revival also fostered a sustainable ecosystem through new agroforestry and livestock programs, eventually leading to the formation of Farmer Producer Organizations (FPOs). The success of this initiative has attracted international delegations from over 30 countries, serving as a powerful global model for how restoring land can truly bring lasting prosperity to life.